2022
DOI: 10.3389/fonc.2021.808291
|View full text |Cite
|
Sign up to set email alerts
|

KB-68A7.1 Inhibits Hepatocellular Carcinoma Development Through Binding to NSD1 and Suppressing Wnt/β-Catenin Signalling

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal malignancies with extremely poor prognosis. Therefore, revealing the critical molecules involved in HCC progression and prognosis is urgently needed. In this study, through combining public dataset and our cohort, we found a novel prognosis-related long non-coding RNA KB-68A7.1 in HCC. KB-68A7.1 was lowly expressed in HCC, whose low expression was associated with large tumour size, aggressive clinical characteristic, and poor survival. Gain- and loss-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, overexpression of KB-68A7.1 reduced proliferation, migration, invasion, and increased apoptosis rates, whereas WNT10B overexpression attenuated these effects. These results suggest a mechanism in which KB-68A7.1 functions as a tumor suppressor by sequestering NSD1 to the cytoplasm and inhibiting the transcription of WNT10B ( Zhang S. et al, 2021 ) .…”
Section: Wnt10b and Cancermentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, overexpression of KB-68A7.1 reduced proliferation, migration, invasion, and increased apoptosis rates, whereas WNT10B overexpression attenuated these effects. These results suggest a mechanism in which KB-68A7.1 functions as a tumor suppressor by sequestering NSD1 to the cytoplasm and inhibiting the transcription of WNT10B ( Zhang S. et al, 2021 ) .…”
Section: Wnt10b and Cancermentioning
confidence: 92%
“…In vivo , WNT10B knockdown and NSD1 knockout were sufficient to reduce tumor volume and weight, and the combination knockdown/knockout further suppressed tumor volume and weight and reduced pulmonary metastasis significantly ( Zhang et al, 2019 ). Using The Cancer Genome Atlas Liver Hepatocellular Carcinoma dataset, Zhang S. et al (2021) identified the lncRNA KB-68A7.1, which inversely correlated with HCC prognosis. In their model system, they found that expression of KB-68A7.1 reduced the demethylation of histone 3 at lysine 36 (H3K36me2) and increased histone 3 lysine 27 trimethylation (H3K27me3) at the WNT10B promoter to decrease WNT10B expression.…”
Section: Wnt10b and Cancermentioning
confidence: 99%
“…The following immunohistochemical stainings were applied using commercially available and validated antibodies: CD3 (mouse monoclonal anti-CD3, dilution 1:100, Cat# MA1-80469, RRID: AB_928106 , ThermoFisher, Waltham, MA, USA), CD68 (mouse monoclonal anti-CD68, Cat# MA5-13324, RRID: AB_10987212 , ThermoFisher, Waltham, MA, USA), 24 CD20 (mouse monoclonal anti-CD20, dilution 1:100, Cat# sc-70582, RRID: AB_1120279 , Santa Cruz Biotechnology, Dallas, TX, USA), Toll-like receptor 4 (TLR4; mouse monoclonal anti-TLR4, dilution 1:200, Cat# ab22048, RRID: AB_446735 , Abcam, Cambridge, UK), cleaved caspase 3 (CCasp3; polyclonal anti-CCasp3, dilution 1:400, Cat# 9661, RRID: AB_2341188 , Cell Signaling Technology, Danvers, MA, USA). 25 Scoring was based on the H-Score previously described elsewhere. 26 …”
Section: Methodsmentioning
confidence: 99%
“…NSD1 promotes the progression of acute myeloid leukemia, multiple myeloma, and lung cancer, as well as cancer cell migration and invasion in hepatocellular carcinoma (HCC), pediatric glioma, and breast cancer [ 90 95 ]. The carcinogenic potential of NSD1 is mediated via activation of Wnt/β-catenin signaling [ 90 , 94 ].…”
Section: Histone H3k36 Di-methyl Transferasesmentioning
confidence: 99%